THE PLACE OF WINE TOURISM IN THE NATIONAL ECONOMY OF UZBEKISTAN - Jalilov Shokhjakhon Kholbozor ugli (Modern American Journals, 2025)
The article analyzes the concept of wine (eno) tourism, its development experiences in the world, and the opportunities for the formation of this type of tourism in the republic. The main attention is paid to the experiences of regions such as Tashkent, Samarkand regions and the Fergana Valley, which have successfully established wine (eno) tourism, and their place in the economy of the republic. Conceptual and practical proposals are put forward for the development of wine tourism in the republic.
Keywords: Tourist, wine tourism, excursion, branding, agro-ecotourism, gastronomic, ethnographic, integration, infrastructure, wine festival, wine museum, cluster.